(untitled) (Research, Society and Development, 2020)
Objectives: To identify the main problems in Primary Health Care, faced by nurses, Describe the skills of the nursing staff in Primary Health Care and discuss the limits and possibilities of Primary Health Care of the population in the Primary Health Network, based on the nurses’ competences. This is a descriptive exploratory study, which aims to clarify and provide an overview in broader dimensions about a given fact. Semi-structured interviews were carried out with 10 nurse managers of Primary Health Care. The scenarios chosen for the research were the Family Medical Program (PMF) Vital Brazil, the Policlínica Regional Carlos Antônio da Silva and the Clínica Comunitária da Família do Badu, both in the city Niterói (RJ- Brazil), and a Type A Unit in the West Zone of Rio de Janeiro. The questions mainly dealt with problematic situations in the daily work and which management strategies and attitudes were taken to solve or reduce each one. It was concluded that it is necessary to make efforts in the permanent training of nurses, in order to achieve the managerial competences, increasingly required by the world of work.